Home gardens for improved food security and livelihoods - Dissanayake, D. Hashini Galhena; Maredia, Karimbhai M. (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
"Home Gardens for Improved Food Security and Livelihoods demonstrates how home gardens hold particular significance for resource-poor and marginalized communities in developing countries, and how they offer a versatile strategy towards building local and more resilient food systems. With food and nutritional security being a major global challenge, there is an urgent need to find innovative ways to increase food production and diversify food sources while increasing income-generating opportunities for communities faced with hunger and poverty. This book shows that, when implemented properly, home gardens can become just such an innovative solution, as well as an integral part of sustainable food security programmes. It provides a conceptual overview of social, economic, environmental, and nutritional issues related to home gardening in diverse contexts, including gender issues and biodiversity conservation and presents case studies from Africa, Asia and Latin America, highlighting home gardening experiences and initiatives. The volume concludes with a synthesis of key lessons learned and ways forward for further enhancing home gardens for sustainable food security and development. This book will be of paramount importance to students and academics working on local food systems, urban food and food security and sustainable development more broadly"--
OCLC-licensed vendor bibliographic record.
Keywords: Vegetable gardening -- Developing countries; Food security -- Developing countries; TECHNOLOGY / Agriculture / Tropical Agriculture